IMPROVEMENT OF TECHNOLOGY CREATION OF MULTIMEDIA ELECTRONIC TEXTBOOKS ON "INFORMATICS AND INFORMATION TECHNOLOGY" FOR SCHOOLS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In work the questions of improvement of technology creation of multimedia electronic textbooks on "Informatics and information technology" for general education schools are considered.